University teachers, their students and ELF pronunciation: attitudes to models, accommodation and identity - Josipović Smojver, Višnja (2013)
University teachers, their students and ELF pronunciation: attitudes to models, accommodation and identity This paper is set within the framework of current ELF research dealing with ELF pronunciation and the attitudes towards it (Jenkins et. al. 2011 ; Seidlehofer 2004). Attitudes to ELF pronunciation in Croatia vary primarily depending on the profile and personality of the ELF user (Stanojević & Josipović 2011), which is largely in line with results of research from other countries (Pitzl & Ehrenreich 2012 ; Pennycook 2009). In this paper we address the interaction of higher education teacher-student attitudes to ELF pronunciation in Croatia. More specifically, we interviewed English university teachers from 15 different higher education institutions (e.g. business, law, humanities, air traffic, etc.) to find out their attitudes towards pronunciation and compared these results with a survey of attitudes of their students (Authors 2011). We focused on the following issues: (a) the importance which the teachers/students attach to pronunciation ; (b) pronunciation models which the teacher finds appropriate and the students aspire to ; (c) the degree of tolerance to the mixing of pronunciation models and exposure to a wide range of pronunciation types ; (d) awareness of the strategies of developing flexibility and accommodation skills in a multilingual/multicultural setting ; and (e) a general attitude towards ELF pronunciation and its relationship with one's identity. These results were compared with the results of the student survey (N=1461) and related to the type of educational institution. Pronunciation is not the real focus of teaching, though there are notable cases when participants make a point of demonstrating their own learning capabilities by approaching native-like pronunciation. Accordingly, the university teachers do not attach much importance to the development of special accommodation skills and strategies. Still, the social (exclusionary/inclusionary) potential of certain pronunciation models is recognized by the teachers and students. Based on this, we discuss the implications of the present research for English teaching at university level in Croatia. References Jenkins, J., A. Cogo and M. Dewey (2011). Review of developments in research into English as a lingua franca. Lang.Teach, 44.3, 281-315. doi: 10.1017/S0261444811000115. Pennycook, A. (2009). Plurilithic Englishes: Towards a 3D Model. In K. Murata and J. Jenkins (eds.), Global Englishes in Asian contexts. Basingstoke: Palgrave Macmillan, 194-207. Pitzl, M.-L. and S. Ehrenreich (2012). Preparing Teachers for an ELF Future: What We CAN Tell Them. Paper presented at ELF5 – The Fifth Conference of English as a Lingua Franca, May 24-26, 2012, Istanbul, Turkey. Book of abstracts: p.16. Seidlhofer, B. (2004). Research perspectives on teaching English as a Lingua Franca. Annual Review of Applied Linguistics 24, 209-239. Stanojević, Mateusz-Milan, and Višnja Josipović Smojver. 2011. “Euro–English and Croatian national identity: are Croatian university students ready for English as a Lingua Franca?” Suvremena Lingvistika 37 (71): 105–130.